Prototype Otomatisasi Kendali Pengisian Penampungan Air Berbasis Arduino Uno dan Sensor Ultrasonik - Prasetya, Ananda Yoga; Yuki Novaliandra; Gumilang, Yandhika Surya Akbar (Teknik Elektro Universtias Krisnadwipayana, 2024)
A clean water supply system is one of the basic human needs that must be met in daily life. The availability of sufficient and quality-maintained water is essential for various purposes, including consumption, sanitation, and other domestic activities. One way to ensure water availability is by using a water tank as a storage medium. However, manually managing water tanks often encounters various issues, such as overfill (water overflowing) or water shortages due to human negligence in monitoring the water level in the tank. To improve the efficiency and effectiveness of water tank management, an automatic system is required that can regulate the filling of the tank independently without human intervention. This system uses an ultrasonic sensor and an Arduino Uno to detect the water volume in the tank. When the water volume reaches high or low levels, the system will automatically control the filling of the tank. Testing results show that the device functions well as intended